Secret Key Design Using an Algebraic Procedure (KAP) for Encrypted Energy Internet-of-Things (EIoT) Contents - Al-Ghaili A.M.; Kasim H.; Al-Hada N.M.; Hassan Z.; Omar R.; Othman M.; Shayea I. (Springer Science and Business Media Deutschland GmbH, 2024)
This study designs a secret Key using an Algebraic Procedure (KAP). KAP has the capability to act in a different manner dependent on the plaintext input. Two different secret key length approaches are presented in this work. Increase the unpredictability and privacy of plaintext by using such a scheme is the main objective of this design presented in this paper. A sequence of algebraic procedures has been utilized in order to construct a particular coefficient by which the link between plaintext size and key length is customizable. This design of secret key enhances the privacy of sensitive data notably utilized with smart Internet-of-Things (IoT) based applications. Calculations on how long it takes to produce and encrypt a single secret key have shown that the suggested architecture is efficient. Additionally, the findings have demonstrated that when a directly proportional connection between user entries to size-in-bits, the relationship between user entries and secret key algebraic functions is reversely proportional thus higher unpredictability of plaintext and secret key may be attained. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.